Diversidad de las comunidades de líquenes y briofitas en los fragmentos de bosques de Polylepis del Parque Nacional Cajas - Granda Macas, Dany Gabriel (2018)
Abstract:Polylepis forests has a very humid microenvironment with high diversity of cryptogams playing an key role in water regulation of many wetlands, lagoons and glaciers. We analyzed the richness and composition of lichens and bryophytes in different substrates of fragments of Polylepis forest of Cajas National Park. We selected four plots of 10 x 10 m; in each plot five grids were chosen randomly for the tree, soil and rock with a total of 60 grids. We analyzed the effect of substrate type on richness with generalized mixed models (GLM). We analyzed differences between the lichen and bryophyte communities according to the substrate type with the non-metric multidimensional scaling (NMDS) and permutational multivariate analysis of variance (PERMANOVA). We recorded a total of 82 species, 30 lichens, 28 hepatics and 24 mosses, the most predominant growth forms were foliose in lichens and liverworts and acrocarpous mosses. The Polylepis forests showed a high diversity of cryptogams on differents substrates, therefore the conservation of these forests is important for biodiversity conservation in the Cajas National Park.